Age and Sex Differences in Long‐Term Outcomes Following Implantable Cardioverter‐Defibrillator Placement in Contemporary Clinical Practice: Findings From the Cardiovascular Research Network. Issue 6 (2nd June 2015) - Masoudi, Frederick A.; Go, Alan S.; Magid, David J.; Cassidy‐Bushrow, Andrea E.; Gurwitz, Jerry H.; Liu, Taylor I.; Reynolds, Kristi; Smith, David H.; Reifler, Liza M.; Glenn, Karen A.; Fiocchi, Frances; Goldberg, Robert; et al.
Abstract : Background: Patient sex and age may influence rates of death after receiving an implantable cardioverter‐defibrillator for primary prevention. Differences in outcomes other than mortality and whether these differences vary by heart failure symptoms, etiology, and left ventricular ejection fraction are not well characterized. Methods and Results: We studied 2954 patients with left ventricular ejection fraction ≤0.35 undergoing first‐time implantable cardioverter‐defibrillator for primary prevention within the Cardiovascular Research Network; 769 patients (26%) were women, and 2827 (62%) were aged >65 years. In a median follow‐up of 2.4 years, outcome rates per 1000 patient‐years were 109 for death, 438 for hospitalization, and 111 for heart failure hospitalizations. Procedure‐related complications occurred in 8.36%. In multivariable models, women had significantly lower risks of death (hazard ratio 0.67, 95% CI 0.56 to 0.80) and heart failure hospitalization (hazard ratio 0.82, 95% CI 0.68 to 0.98) and higher risks for complications (hazard ratio 1.38, 95% CI 1.01 to 1.90) than men; patients aged >65 years had higher risks of death (hazard ratio 1.55, 95% CI 1.30 to 1.86) and heart failure hospitalization (hazard ratio 1.25, 95% CI 1.05 to 1.49) than younger patients. Age and sex differences were generally consistent in strata according to symptoms, etiology, and severity of left ventricular systolic dysfunction, except the higher risk of complications in women, which differed by New York Heart Association classification ( P =0.03 for sex–New York Heart Association interaction), and the risk of heart failure hospitalization in older patients, which differed by etiology of heart failure ( P =0.05 for age–etiology interaction). Conclusions: The burden of adverse outcomes after receipt of an implantable cardioverter‐defibrillator for primary prevention is substantial and varies according to patient age and sex. These differences in outcome generally do not vary according to baseline heart failure characteristics.